Automatic diabetic retinopathy detection and classification system - Omar Z.A.; Hanafi M.; Mashohor S.; Mahfudz N.F.M.; Muna'Im M. (Institute of Electrical and Electronics Engineers Inc., 2024)
Indexed by Scopus